Pendidikan Kristen Sebagai Upaya Pembangunan Karakter Bangsa: Studi Kurikulum Di Sekolah Teologi - Kristin Selan (Jurnal Ilmu Agama Indonesia, 2025)
This study analyzes the role of Christian education in the effort to build national character, focusing on the curriculum of theological schools. Character building is viewed as a crucial pillar amidst global challenges, and Christian education offers a strong theological foundation for shaping individuals with integrity. Using a qualitative approach and a case study method, this research examines two theological schools in Indonesia. Data was collected through in-depth interviews with lecturers, students, and alumni, as well as an analysis of curriculum documents and non-participant observation. The findings indicate that character formation occurs through a holistic integration of the formal curriculum, which provides an ethical and theological foundation, with non-curricular activities that facilitate the internalization of practical values such as humility and cooperation. The role of lecturers as role models was also found to be highly significant in influencing students' character development. However, the study also identifies challenges, such as limited resources. Overall, this research concludes that theological schools play a strategic role in producing individuals who are not only theologically competent but also possess a strong character that is relevant to the building of the nation.